Pendampingan Pengembangan Raudhatul Athfal di Yayasan Nahdatul Ulum Kota Sorong - Nasrul Fauzi; Nur Faizah (LPPM IAIN Sorong, 2021)
Abstract This service aims to provide assistance in the development of Raudhatul Athfal's education at the Nahdlatul Ulum Foundation NU Sorong City. Some of the mentoring steps include team preparation, through this activity the team agreed on the appointment of school principals and the recruitment of prospective RA teachers. Socialization and licensing were carried out by the foundation management together with the principal and the teacher council by utilizing social media, visiting the Taklim assembly and at routine dhikr recitations held by PCNU Sorong City. The implementation of the mentoring program in developing RA NU is carried out by supervising learning by the principal and training for existing teachers. The service activities include school management training for RA teachers, training in learning methods and strategies for RA teachers, Comparative Study Activities, Organizing Student Volunteers from the Tarbiyah Faculty of IAIN Sorong, forming a student parent taklim assembly, carrying out Parenting activities, Child Health Consultations and Collaboration with health center doctors and children's learning counseling program. Keywords: Mentoring, Educational Development, Raudhatul Athfal